The Associations of Serum Osteocalcin and Cortisol Levels With the Psychological Performance in Primary Hyperparathyroidism Patients - Wang, Shu-min; He, Yang; Zhu, Min-ting; Tao, Bei; Zhao, Hong-yan; Sun, Li-hao; Liu, Jian-min (Frontiers in Endocrinology, 2021)
Objectives The aim of this study was to investigate factors responsible for the psychological performance in primary hyperparathyroidism (PHPT) patients Methods: A group of 38 PHPT patients receiving questionnaires, including Becking depression inventory (BDI), State-Trait Anxiety Inventory (STAI) and SF-36 were evaluated. The relationships between scores of questionnaires and clinical biomarkers were examined. Collinearity and linear regression model was applied to examine variables determining the sores of questionnaire. In 192 PHPT patients, bivariate and partial correlation was used to analyze the relationships between serum concentrations of parathyroid hormone (PTH), calcium, osteocalcin (OCN), and cortisol concentration. Results Among 38 patients receiving questionnaire tests, 50% (19/38) patients developed state anxiety, 60.5% (23/38) patients had the trait of developing anxiety. 18.4% (7/38) patients developed mild to severe depression. Serum cortisol at 8:00 was negatively and significantly correlated with social function (r=-0.389, P=0.041), after controlling for age, sex, duration, serum PTH, calcium, phosphorus and 25-(OH)D concentration. OCN was significantly and negatively correlated with score of STAI-S (r=-0.426, P=0.027). In the linear regression model for BDI score, variables with statistical significance were serum OCN (β=-0.422, P=0.019) and cortisol at 0:00 (β=0.371, P=0.037). In 192 PHPT patients, the serum concentration of OCN (r=0.373, P=0.000) was positively correlated with PTH level. After controlling for age, sex, disease duration, serum 25-(OH)D, phosphorus and calcium concentration, the positive correlation between OCN and PTH was still statistically significant (r=0.323, P=0.000). The serum concentration of cortisol at 0:00 was significantly and positively correlated with serum calcium (r=0.246, P=0.001) in bivariate correlation analysis. After controlling for age, sex, disease duration, serum PTH, 25-(OH)D and phosphorus concentration, serum cortisol at 0:00 was still positively and significantly correlated with serum calcium (r=0.245, P=0.001). Conclusion Serum levels of OCN and cortisol, rather than PTH and calcium, are associated with development of anxiety and depression symptoms in PHPT patients.